Impacts of an online asynchronous continuing professional development toolkit supporting primary care nurses to engage in shared decision-making: a single-group pre-post study - Marie-Eve Poitras; Vanessa T. Vaillancourt; Priscilla Beaupré; Andréanne Bernier; Karina Prévost; Annie Poirier; Mireille Guérin; Pierre Pluye; Mathieu Bujold; France Légaré; Maud-Christine Chouinard; Catherine Hudon (BMC Nursing)
Abstract Background Shared decision-making (SDM) is central to person-centred care and professional nursing practice. Some primary care nurses must become more comfortable and prepared to use SDM in their practice, especially with patients having complex care needs. Methods We conducted a single-group pre-post study with primary care nurses to assess the relevance and impacts of the online continuing professional development (CPD) toolkit. Using the New World Kirkpatrick model, we assessed the toolkit’s relevance (level-1, reaction) and nurses’ confidence and commitment (level-2, learning). We collaborated with the virtual community of practice for nurses in family medicine groups in Quebec to reach out to as much nurses as possible. We sent hard copies of the toolkit to 42 primary care establishments. We used descriptive statistics and the student t-test to treat quantitative data and analyzed open-ended questions with qualitative content analysis. Results One hundred sixty-five nurses used the toolkit, and 69 completed the pre- and post-training survey. Most were female (94.2 %), aged between 31–45 years old (55.1 %), and held a first university degree (91.3 %). Ninety-six percent (96 %) agreed or strongly agreed that the toolkit would improve their practice. The toolkit significantly increased nurses’ confidence (p ≤ 0.001) and intention (p ≤ 0.01) to engage in SDM with patients having complex care needs. Nurses appreciated the relevance of video vignettes and accessibility, amongst others. Conclusions Primary care nurses felt better able to include SDM in their practice with patients with complex care needs and understand their roles better. A CPD toolkit by and for primary care nurses is relevant and increases learning.